Análise da atitude de jovens universitários com relação ao ciclismo - Dezani, Adriana Alvarenga (Universidade Federal de São Carlos, 2016)
The use of bicycles as a transportation way has been in discussion for some time. Versatile, lightweight, quiet and clean, the bike can be part of the solution to the transport problems that occur in big cities. The increasing saturation of the city roads by automobiles have recently reinforced the importance of bikes, now suggested as an alternative for sustainable mobility. It is has been noticed that it is no longer used just by leisure, sport or toy means, and has definitely become a transport option, either for financial reasons, agility, welfare, health, convenience or due to the deficiency of public transport. In this research we aimed at studying the applicability of the Theory of Planned Behavior in order to analyze the attitude of university students towards cycling, aiming at identifying the behavioral factors that can explain the bike option for utility trips (to work and to school). The methodology has started by the bibliographic research in order to identify the factors that influence the attitude towards cycling, followed by the development of the survey instrument. Targeting this end, we have developed a questionnaire based on the three constructs of Planned Behavior Theory and based on observable variables on the habit and intention in using the bike, betaking the Google Drive tool for this purpose. The questionnaire was sent via email to undergraduates and also it was applied in classrooms, with the authorization of the professors in four public universities (one in each city). From the 1,200 questionnaires sent 705 valid forms were answered on a proper way. The data collection for this research was carried out in public institutions of higher education in São Carlos - SP, São José do Rio Preto - SP, Campo Grande - MS and Tupã - SP. For data analysis, we have used confirmatory factor analysis, factor analysis and cluster analyzes. The survey results allow a better understanding about the construct Attitude towards bicycle use.Throughout the study it was identified that the construct Attitude comes to be represented by three factors: Quality (Health, Economy, Environment), Freedom (Independence, Speed) and Insecurity (accidents, robbery). Another remark was that not always the more positive value for the attitude implies ona strong intention to use the bike. It is considered that this research reached its main goals and the results contribute to the settlement of the policy guidelines encouragement on using bicycles on utilitarian trips, given that the implementation of a program to encourage the use of bicycle policy can bring economic and environmental benefitsfor a city.
Keywords: Ciclismo; Equação estrutural; Teoria do comportamento planejado; Cycling; Structural equation; Theory of planned behavior; ENGENHARIAS; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::VEICULOS E EQUIPAMENTOS DE CONTROLE::VEICULOS DE TRANSPORTES